Analisis Ungkapan Idiomatik pada Buku Siswa Kelas II Tema 1 Sub Tema 1 - Avifah, Dwi Putri Eka Ratna; Nurhayati, Eni (Lembaga Penelitian dan Pendidikan Mandala, 2022)
Analysis of Idiomatic Expressions in Student Book of Class Two Theme 1 and Sub-theme 1.This study aimed to describe the results of the analysis that associated with the kind, structure and meaning of idiomatic expressions in the second-grade student book, theme 1: Living in Harmony. This study used a descriptive qualitative approach by analyzing qualitative data within the kind words or sentences that containing idiomatical expressions. Among ten idiomatic expressions, there are two partial idioms and eight full idioms. The structure of the idioms was (1) noun + noun, (2) adjective + noun, and (3) noun + adjective. Regarding on the meaning, there are idiomatic expressions that still have a connection with the lexical meaning of one of its constituent elements. However, most of the idiomatic expressions that have emerged have new meanings that are completely separated from the lexical meaning of the constituent words. The Idiomatic Expressions that contained in Student Book of class II Theme 1 Sub theme 1 are in the line with development of students who have just started learning in class 2 and already have knowledge about nouns and adjectives.